The Role of Parents in Instilling Honesty in Children at SDN 55 Otting - Takbir, Takbir; Sulferawati, Sulferawati; Wahyudi, Rizky; Nurul Sari Mansur, Desya; Sulfiana, Sulfiana (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2024)
This study aims to describe how the role of parents in instilling honesty in children. The stages of character formation will be correlated with psychological theory. This research is a descriptive qualitative research with an approach single case study to a complex and comprehensive picture obtained from informants, as well as the research background as it is. Data collection teachique in his study are interviews, observation and documentation. Character building honesty in children in the family is very important family is the first environment a place where children grow develop and build a personality that will become their identity later. Exemplary and direct examples of honesty that parents do will be embedded in child’s memory. Familiarizing children to be honest with themselves is the beginning of the formation of honeaty for the capital of his life. The intensity of the presence, the caress of affection, the warmth and attention that parents give their children play an imporatant role in shaping honesty character. Teachers also play an important role in forming honesty characters in children when they are taught school by setting an example and honest behavior. The result of the study foud that forming honesty character, children are not only equipped with cognitive knowledge about honesty but also must to the affective domain and implemented in real behavior.